SUBSURFACE VELOCITY MODEL FROM INVERSION OF H/V SPECTRAL RATIO OF AMBIENT NOISE RECORDS - Titi Anggono; Syuhada Syuhada (Program Studi Fisika Universitas Negeri Jakarta, 2017)
Abstract The Horizontal-to-Vertical (H/V) spectral ratio method uses continuous ambient noise records has been used extensively to study the characteristics of site response due to the earthquake occurrence. Sources of ambient noise are usually from human activities or natural excitations and might be composed of body and surface wave components. Several studies have investigated the possibility to extract information on the shallow subsurface model from the inversion of H/V spectral ratio. In this study, we investigated the shallow subsurface velocity model below two broadband seismometers at Simeulue Island, Aceh. Two broadband seismometers of PUTR and LEWK were selected because of the relatively clear peak amplitude of H/V spectral ratios, which may reflect the existence of strong impedance contrast. The initial models are set to be fixed of five homogeneous medium layers with the last medium to be infinite homogeneous medium. By setting fixed layer boundaries in the inversion process, the velocities in the medium may vary to obtain the most suitable fitting to the observed H/V spectral ratio. From the inversion process, we suggest we suggest that the strong impedance contrasts may occur on the shallow part of the medium at 2 up to 15 m depth. Keywords: ambient noise records, H/V spectral ratio, inversion process.